Editorial knowledge and skills in the scholastic profession of Ukrainian language and literature - Diana Pryndyuk (Інтегровані комунікації, 2016)
The article considers the aspects of development of professional competence of the editor as a lecturer of Ukrainian language and literature; it analyses the editor’s skills as a subject of sphere of pedagogical activities. After all, the modernization of vocational education in Ukraine is impossible without formation of a competent, highly skilled pedagogue whose knowledge basis will meet international standards. In recent years, the combination of types of professional competence of the teacher is constantly replenished, the modern educational paradigm is oriented not only to the high level of knowledge of didactic material, but also to search for new methods of information transmission, developing a range of all potential opportunities in the system of future teacher training. The scope of the editor's activity is noticeably expanded, and it is not only the publishing house, editorial staff of newspapers and magazines, the employer invests in the notion of “editor” the maximum of everything that is needed for the effective functioning of the organization, provision of publishing products, and the establishment of relations with the public. An actual theme of modern education is awareness of the problem of a new model of education, which aims to form such a specialist of the Ukrainian language and literature, the level of preparation of whom combines education, professionalism, creative abilities. The prospect of building a knowledge society in Ukraine requires a profound reform of the educational sphere, which should be realized on the basis of a reasonable combination of better foreign experience with national traditions. Taking advantage of the experience of editorial profession, the teacher in some way reformes the pedagogical education, increases the efficiency of complex of students knowledge, encouraging them to new approaches to learning and developing their own individual abilities. The objective of the study is to determine the principles of professional competence of the editor as a teacher of the Ukrainian language and literature.